Combined resection of aberrant right hepatic artery without anastomosis in panceaticoduodenectomy for pancreatic head cancer: A case report. (2016) - Nanashima, Atsushi; Imamura, Naoya; Tsuchimochi, Yuki; Hiyoshi, Masahide; Fujii, Yoshiro
Highlights: The aberrant right hepatic artery is often arising from superior mesenteric artery. Combined resection of the aberrant right hepatic artery is necessary in pancreaticoduodenectomy for pancreatic head cancer to achieve R0 resection. Arterial anastomosis of combined resection is not always necessary because of existence of communicating artery from the middle and left hepatic artery via hepatic hilar plate. R0 resection without tumor exposure at the dissected plane improves prognosis of pancreatic cancer patients. Abstract: Introduction: This case report is intended to inform pancreas surgeons of our experience in operative management of aberrant pancreatic artery. Presentation of case: A 63-year-old woman was admitted to our institute's Department of Surgery with obstructive jaundice, and the pancreas head tumor was found. To improve liver dysfunction, an endoscopic retrograde nasogastric biliary drainage tube was placed in the bile duct. Endoscopic fine-needle aspiration showed a pancreas head carcinoma invading the common bile duct, the aberrant right hepatic artery arising from the superior mesenteric artery, and the portal vein. Enhanced computed tomography showed the communicating artery between the right and left hepatic artery via the hepatic hilar plate. By way of imaging preoperative examination, a pancreaticoduodenectomy combined resection of the aberrant right hepatic artery and portal vein was conducted without arterial anastomosis. Hepatic arterial flow was confirmed by intraoperative Doppler ultrasonography, and R0 resection without tumor exposure at the dissected plane was achieved. The patient's postoperative course was uneventful. Discussion: In this case report, perioperative detail examination by imaging diagnosis with respect to hepatic arterial communication to achieve curative resection in a pancreas head cancer was necessary. Non-anastomosis of hepatic artery was achieved, and the necessity of R0 resection was stressed by such management. Conclusion: By the preoperative and intraoperative imaging managements conducted, combined resection of the aberrant right hepatic artery without anastomosis was achieved by pancreaticoduodenectomy for pancreas head cancer. However, improvements in imaging diagnosis and careful management of R0 resection are important.